The Poulterers' Case (1611): A Landmark in the History of Criminal Conspiracy - Saucedo Maqueda, Víctor Manuel (Historia del Derecho, 2021)
Every student of criminal law knows for a fact that the Poulterers' Case (1611) launched modern criminal conspiracy. This decision laid the first stone of the principle that an agreement to commit a crime is also a crime. However, besides what the law reports say, little is known about the facts of the case. This edition of the testimonies collected by the Star Chamber intends to fill this gap. Additionally, an introductory study will discuss how these facts shed new light on the reasons that were mustered in support of the decision. It will also argue that modern conspiracy was not a creation of the courts but rather of the nineteenth-century scholars who turned the Poulterers' Case into a landmark case.---Todo estudiante angloamericano de derecho penal sabe que el Poulterers's Case (1611) dio el primer paso hacia el delito moderno de conspiración en Inglaterra. Esta decisión puso la primera piedra del principio según el cual con el acuerdo para cometer un delito se comete ya un delito. Sin embargo, aparte de lo que dicen los law reports, poco se sabe de los hechos del caso. Esta edición de los testimonios recogidos por la Star Chamber pretende colmar esta laguna. Además, un estudio introductorio analizará cómo estos hechos arrojan luz sobre las razones que se esgrimieron en apoyo de la decisión. También se argumentará que la conspiración moderna no fue una creación de los tribunales, sino de los juristas del siglo XIX que convirtieron el Poulterers' Case en un hito jurisprudencial.